Cyberbullying and Electronic Aggression as a Current Threat of Network Communication - Dyrla-Mularczyk, Karolina; Pluciński, Mateusz (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The Internet is a medium used for sharing various kinds of content. Its role in technology development, spread and accessibility of knowledge is essential. Internet also comes with certain risks, and one of the most important is the appearance of cyberbullying which is contemporary youth mobbing that moved on-line. The study defines the phenomenon of cyberbullying and presents forms that it takes. Moreover, the victims and the perpetrators of such violence were characterized and the results of the survey conducted in a group of students that demonstrate their personal experiences were discussed. Opportunities to prevent aggressive behavior on-line were also presented.